Answer:
[tex]y=89.99+36.55\left(x-1\right)[/tex] can be written as [tex]y=36.55x+53.44[/tex] which is into the form [tex]y=ax+b[/tex].
Step-by-step explanation:
Considering the expression
[tex]y=89.99+36.55\left(x-1\right)[/tex]
[tex]y\:=89.99+36.55x-36.55[/tex]
[tex]y=36.55x+53.44[/tex]
writing into the form of the equation
[tex]y=ax+b[/tex]
so
[tex]y=36.55x+53.44[/tex]
Here:
Therefore, [tex]y=89.99+36.55\left(x-1\right)[/tex] can be written as [tex]y=36.55x+53.44[/tex] which is into the form [tex]y=ax+b[/tex].